2009
DOI: 10.1111/j.1728-4465.2009.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Multidimensional Measure of Pregnancy Intentions: Evidence from the United States

Abstract: Widely used dichotomous categorical measures of pregnancy intentions do not represent well the complexity of factors involved in women's intentions. We used a variety of exploratory statistical methods to examine measures of pregnancy intention in the 2002 National Survey of Family Growth (N = 3,032 pregnancies). Factor analyses identified two key dimensions of pregnancy intentions (desire and mistiming) and two smaller nondimensional categories (overdue and don't care). Desire included both affective and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(230 citation statements)
references
References 42 publications
(58 reference statements)
11
213
1
5
Order By: Relevance
“…Schaeffer and Thomson's (1992) study, providing ample evidence that routine survey questions are insufficient to capture the quality and degree of respondents' uncertainty, together with Thomson and Brandreth (1995), would make an excellent starting point. Recent research on improving measures of pregnancy intendedness is a further resource (Kaufmann et al 1997;Bachrach and Newcomer 1999;Stanford et al 2000;Barrett et al 2004;Stevens-Simon et al 2005;Santelli et al 2009;Schwartz et al 2010). Third, another approach to measuring expectations and intentions is using probabilistic questions to elicit an assessment of level of certainty in continuous rather than classified form (Burden 1997;Manski 2004;Delavande 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Schaeffer and Thomson's (1992) study, providing ample evidence that routine survey questions are insufficient to capture the quality and degree of respondents' uncertainty, together with Thomson and Brandreth (1995), would make an excellent starting point. Recent research on improving measures of pregnancy intendedness is a further resource (Kaufmann et al 1997;Bachrach and Newcomer 1999;Stanford et al 2000;Barrett et al 2004;Stevens-Simon et al 2005;Santelli et al 2009;Schwartz et al 2010). Third, another approach to measuring expectations and intentions is using probabilistic questions to elicit an assessment of level of certainty in continuous rather than classified form (Burden 1997;Manski 2004;Delavande 2008).…”
Section: Discussionmentioning
confidence: 99%
“…First, abortion surveillance is needed to guide and evaluate the success of programs aimed at preventing unintended pregnancies. Although pregnancy intentions can be difficult to assess (79)(80)(81)(82)(83)(84), abortion surveillance provides an important measure of pregnancies that are unwanted. Second, routine abortion surveillance is needed to assess trends in clinical practice patterns over time.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…We did note a correlation between the outcome as measured and women reporting being ''very happy'' about their pregnancy (AOR, 95% CI for the outcome 0.46, 0.25-0.86 among women who were ''very happy''), a suggestion that our measure may track with intent. Santelli et al 33 recently reported a moderate correlation between trying to get pregnant and happiness about pregnancy and described ''trying'' as one cognitive factor predictive of pregnancy intent. 34 Other measures have endured varied criticisms of their ability to measure unintended pregnancy as well, and currently there is no gold standard for the determination of pregnancy intent.…”
Section: Bryant Et Almentioning
confidence: 99%